PROBLEMATIC INTERNET USE (PIU) IDENTIFICATION USING THE BIOPSYCHOSOCIAL MODEL APPROACH IN EMERGING ADULTHOOD - Rahayu, Aneke Dewi; Prasetyoaji, Ari (Universitas Teknologi Yogyakarta, 2020)
Individuals with Problematic Internet Use (PIU) who use the internet excessively, it gave the causes of the difficulties to control using the internet and bad impact of physical and mental disorder. The research aims to show the relationship among biological, psychological, and social factors with PIU so it can be created some relation model which explain about this phenomenon. Simple random sampling is a sampling technique used of this research. Subjects used of this research were 403 individuals who were in the age of emerging adulthood. Data collection method used in this research is PIU and bio psychosocial scale which consists of three parts are biology, psychology, and social. Based on the data processing, a relationship model among biology, psychology, social, and PIU where the relationship model has a chi square score of 0.102 with a probability score of 0.061, a CMIN / DF score of 1.518, a GFI of 0.919, an AGFI of 0.971, a CFI equal to 1.00, TLI of 0.90, and the score of RMSEA 0.072 so the model was proposed as strong and acceptable category. The model shows strongest relationship is the relationship between social and PIU was 0.47, psychology with PIU was 0.22, and biology with PIU was 0.12.